Supplemental dietary phytosterin protects against 4-nitrophenol-induced oxidative stress and apoptosis in rat testes. (2015) - Zhang, Yonghui; Song, Meiyan; Rui, Xiaoli; Pu, Shaoxia; Li, Yansen; Li, ChunMei
Abstract: 4-Nitrophenol (PNP), is generally regarded as an environmental endocrine disruptor (EED). Phytosterin (PS), a new feed additive, possesses highly efficient antioxidant activities. The transcription factor, nuclear factor-erythroid 2-related factor 2 (Nrf2), is an important regulator of cellular oxidative stress. Using rats, this study examined PNP-induced testicular oxidative damage and PS-mediated protection against that damage. The generation of MDA and H2 O2 upon PNP and PS treatment was milder than that upon treatment with PNP alone. This mitigation was accompanied by partially reversed changes in SOD, CAT, GSH and GSH-Px. Moreover, PNP significantly reduced the caudal epididymal sperm counts and serum testosterone levels. Typical morphological changes were also observed in the testes of PNP-treated animals. PNP reduced the transcriptional level of Nrf2, as evaluated by RT-PCR, but it promoted the dissociation from the Nrf2 complex, stabilization and translocation into the nucleus, as evaluated by immunohistochemistry and Western blotting. In addition, PNP enhanced the Nrf2-dependent gene expression of heme oxygenase-1 (HO-1) and glutamate–cysteine ligase catalytic subunit (GCLC). These results suggest that the Nrf2 pathway plays an important role in PNP-induced oxidative damage and that PS possesses modulatory effects on PNP-induced oxidative damage in rat testes.